The Impact of Tariff Reduction on Poverty in Indonesia: Regional Level Analysis - Rizka Aulia; Kangkook Lee (Pusbindiklatren Bappenas, 2021)
The study examines the effect of trade liberalization on poverty reduction across districts in Indonesia during the period from 2000 to 2016 using the fixed effect approach. Tariff exposure is used to measure trade liberalization, which is computed at the district level by combining information on sector composition of the economy in each district and tariff lines by sectors. This study also distinguishes between tariff exposure for output products and intermediate inputs. This produces a measure indicating how changes in exposure to tariff reductions in outputs and inputs vary by region over the period. Due to the available multi-district and 17-year dataset, the study includes a set of fixed effects: the district-fixed effects and the time-fixed effects, which controls for aggregate time trend. The results indicate that the impact of output and input tariff on regional poverty headcount index (P0) is different. Output tariff has a negative correlation with poverty, while input tariff has a positive correlation with poverty. This suggests that trade liberalization in input sectors could reduce poverty in Indonesia. It is also found that GRDP per capita, literacy rates, and road length are negatively associated with poverty. Also, the effect of reducing input tariffs on poverty reduction will be larger if the districts have higher GRDP per capita and higher literacy rates.